Reward’s Impact on Motivation to Learn Arabic: Āśaru al-Mukāfa’ah ‘alā al-Dāfi’ li Ta’allum al-Lugah al-‘Arabiyyah - Yanti, Dira; Amiruddin, Amiruddin; Ayu, Sovia Mas; Aridan, Muhammad (Aphorisme: Journal of Arabic Language, Literature, and Education, 2023)
This research aims to determine the influence of rewards on the interest and learning motivation of seventh-grade students at MTs Diniyah Putri Lampung in learning the Arabic language. This type of research uses a quantitative approach with two independent variables and one dependent variable. The primary data in this study are the students' interest and learning motivation in Arabic. In contrast, the secondary data are literature and previous research on the influence of rewards on students' interest and learning motivation. The population in this study consists of seventh-grade students at MTs Diniyah Putri Lampung, with class 7A as the research sample. The data collection techniques used in this study include questionnaires, documentation methods, observation, and interviews. The results of this study were analyzed using multiple regression analysis. They showed an influence between the Reward variable (x) and the Interest variable (y) with a coefficient of determination (R Square) of 0.548, which implies that the Reward variable (x) has a 54.8% influence on the Interest variable (y). There is also an influence between the Reward variable (x) and the Learning Motivation variable (z) with a coefficient of determination (R Square) of 0.411, indicating that the Reward variable (x) has a 41.1% influence on the Learning Motivation variable (z). Additionally, there is an influence between the Interest variable (y) and the Learning Motivation variable (z) with a coefficient of determination (R Square) of 0.432, indicating that the Interest variable (y) has a 43.2% influence on the Learning Motivation variable (z). Finally, there is an influence between the combined Reward variable (x) and the Interest variable (y) on the Learning Motivation variable (z) with a coefficient of determination (R Square) of 0.688, indicating that the Interest variable (y) has a 68.8% influence on the Learning Motivation variable (z).